City climate and landscape structure shape pollinators, nectar and transported pollen along a gradient of urbanization. Issue 6 (2nd May 2022) - Biella, Paolo; Tommasi, Nicola; Guzzetti, Lorenzo; Pioltelli, Emiliano; Labra, Massimo; Galimberti, Andrea
Abstract: Urbanization gradients influence both landscape and climate and provide opportunity for understanding how plants and pollinators respond to artificially driven environmental transitions, a relevant aspect for the ecosystem service of pollination. Here, we investigated several aspects of pollination along an urbanization gradient in landscape and climate. We quantified wild hoverfly and bee abundances with trapping, standing crop of nectar with spectrophotometer, and the pollen transported by flower visitors with DNA metabarcoding, in 40 independent sites from semi‐natural to built‐up areas in Northern Italy. Direct and indirect effects were fitted considering landscape and climate variables. Linear and nonlinear relationships were detected along the urbanization gradient. Pollinator abundances increased quadratically and peaked at 22% of impervious cover with an 81% growth, and they decreased with green‐patch distance by 37% and urban park largeness by 60%. This indicates that pollinators are more abundant at intermediate levels of urbanization. Climatically, pollinators diminished by up to 46% in areas with low spring–summer temperature seasonality: urban areas likely posing thermic stress. Furthermore, the sugar mass available in nectar increased by 61% with impervious cover and by 79% with precipitations, indicating that city nectars were less consumed or flowers more productive. Furthermore, the species richness of pollen decreased by 32% in highly urbanized areas, and contained a high incidence of exotic plants, hinting for anthropized, simplified plant communities. Synthesis and applications . Urbanization influences pollinator abundances, nectar resources and transported pollen in direct and indirect ways. Pollinators are negatively affected by a thermally harsh climate in highly urbanized areas with isolated green areas and large parks. Suburban landscapes demonstrated the highest pollinator presence. In the city core, flowers contained more nectary sugar in association with more precipitations, while pollinators collected pollen from a small number of plants, mainly exotic. These findings highlight the strong influence of urban landscape and climate on pollinators and plants, showing that cities are heterogenous realities. Patterns from this study will serve as basis for pollinator‐friendly planning, mitigation and management of urban landscapes. Abstract : Urbanization influences pollinator abundances, nectar resources and transported pollen in direct and indirect ways. Pollinators are negatively affected by a thermally harsh climate in highly urbanized areas with isolated green areas and large parks. Suburban landscapes demonstrated the highest pollinator presence. In the city core, flowers contained more nectary sugar in association with more precipitations, while pollinators collected pollen from a small number of plants, mainly exotic. These findings highlight the strong influence of urban landscape and climate on pollinators and plants, showing that cities are heterogenous realities. Patterns from this study will serve as basis for pollinator‐friendly planning, mitigation and management of urban landscapes.